All Days 2002
DOI: 10.2118/77449-ms
|View full text |Cite
|
Sign up to set email alerts
|

Filtercake Cleanup Techniques for Openhole Water Injectors with Sand Control: Lessons from Laboratory Experiments and Recommendations for Field Practices

Abstract: Many water injection wells in sand control environments are being completed as open holes because of the higher injectivities attainable with open-hole completions. The sandcontrol techniques used in these wells varies from standalone screens or slotted liners (including expandable screens) to gravel packing. In field practice, the drilling fluids used for injectors have also varied from water-based (either sizedCaCO3/Polymer or sized-salt/polymer) fluids to oil-basedsystems. Although a cake cleanup followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…• It is easy to clean up its filter cake through simple protonation of the emulsifier and conversion of its filter cake from oil-wet to water-wet state, as is well documented in the literature (Dick et al 2003;Parlar et al 2002;Ali et al 2006).…”
Section: Reservoir-drilling-fluid Selectionmentioning
confidence: 90%
See 1 more Smart Citation
“…• It is easy to clean up its filter cake through simple protonation of the emulsifier and conversion of its filter cake from oil-wet to water-wet state, as is well documented in the literature (Dick et al 2003;Parlar et al 2002;Ali et al 2006).…”
Section: Reservoir-drilling-fluid Selectionmentioning
confidence: 90%
“…Initially, inclusion of a cleanup chemical in the carrier fluid was considered to provide simultaneous gravel-pack and filter-cake cleanup, since the RSBM is in fact ideal for such an application (Parlar et al 2002;Ali et al 2006). However, additional testing indicated that the concentration of the breaker needed to achieve an efficient filter-cake cleanup had a negative effect on the particular VES fluid's gravel-suspension capability.…”
Section: Gravel-pack-fluid Selectionmentioning
confidence: 99%